Slang Words In Crank Ii : High Voltage Movie Directed By Taylor And Naveldine - Yanti Rosalinah (Wanastra: Jurnal Bahasa dan Sastra, 2015)
The objective of this research is to analyze slang words in Crank II movie. The method used descriptive qualitative method. The data were collected through watching the full movie, library and internet research. The first analysis of the research is about characteristics of slang that found in the movie, which is divided into: Creative, Vulgar, and Short Lived. Then the second analysis is about functions of slang in the movie and the third or the last is about expressed of slang in the movie, which include: Expressed Love, Disappointed, Shock, and Anger. The results of this research indicated that: (1) It would get and gain the knowledge about slang language through this research paper. (2) The writer suggests that studying about slang language is very interesting, the writer hopes by studying slang language will help the reader to increase new vocabulary about slang. It also hopes that the readers can understand the sociolinguistic of slang that may appear in the learning process (3) the writer hopes that this paper will be useful for all people who want to do research regarding slang.